A Morphological Study Of Affixes Found In Campus English Magazine - Alfianto, Qiyat; , Dra. Malikatul Laila, M. Hum; , Dr. Dwi Haryanti, M.Hum (2014)
This research aims to identify the kinds of affixes, and to explain the forms and meaning of each affixes in Campus English Magazine. The study used descriptive qualitative research to study words which contain prefixes and suffixes. The data are taken from Campus English Magazine volume 52/XII/2012. The data are studied by using Katamba's morphological analysis (1994) and Katamba's word formation (1994). Based on the research finding, first, the researcher finds that in derivational affixes,the researcher finds seven noun indicators which have a form as a suffix such as {-er}, {-ment}, {-ness}, {-ity}, {-ist}, {-ion/ -ation}, and {-ship}. The researcher also finds five adjective indicators which have a form as a suffix such as {-ive}, {-able}, {-al}, {-est}, and {-ful} and a form of prefix, namely prefix {in-}. The researcher only finds an adverb indicator, namely suffix {-ly} and only finds a verb indicator, namely suffix {-ize}. Moreover, inflectional affixes, the researcher only finds a noun indicator, namely suffix {-s} and an adjective indicator, namely suffix {-ing}. The researcher also finds two adjective indicators, namely suffix {-ed} and {-ing}.The writer found a prefix (prefix -in) which can be attached to adjective. Prefixes {-in} form adjective from which originally has a form of adjective. Meanwhile, there are sixteen kinds of suffixes and each suffix can only be attached to noun, verb, adverb and adjective. Suffixes have seven form, namely to form adverb from adjective, noun from verb, noun from adjective, adjective from verb, adjective from noun, verb from noun, adverb from noun, and verb from adjective. Second, the meaning of the affixes that is used Campus English Magazine show the indicators of changing the class of category.